Depot-specific and GH-dependent regulation of IGF binding protein-4, pregnancy-associated plasma protein-A, and stanniocalcin-2 in murine adipose tissue. (April 2018) - Hjortebjerg, Rikke; Berryman, Darlene E.; Comisford, Ross; List, Edward O.; Oxvig, Claus; Bjerre, Mette; Frystyk, Jan; Kopchick, John J.
Abstract: Introduction: Pregnancy-associated plasma protein-A (PAPP-A) stimulates insulin-like growth factor (IGF)-I action through proteolytic cleavage of IGF binding protein-4 (IGFBP-4). Recently, stanniocalcin-2 (STC2) was discovered as an inhibitor of PAPP-A. Most members of the IGF system are expressed in adipose tissue (AT), but there is a relative paucity of information on the distribution of IGFBP-4, PAPP-A, and STC2 in different AT depots. Since IGF-I expression in AT is highly GH-dependent, we used bovine GH transgenic (bGH) and GH receptor knockout (GHR−/−) mice to investigate AT depot-specific expression patterns of IGFBP-4, PAPP-A, and STC2, and whether the regulation is GH-dependent. Methods: Seven-month-old male bGH, GHR−/− and wild type (WT) control mice were used. Body composition was determined, and subcutaneous, epididymal, retroperitoneal, mesenteric and brown adipose tissue (BAT) depots were collected. RNA expression of Igfbp4, Pappa, and Stc2 was assessed by reverse transcription quantitative PCR and IGFBP-4 protein by Western blotting. Results: Igfbp4, Pappa, and Stc2 RNA levels were differentially expressed in an AT depot-dependent manner in WT mice. Igfbp4 RNA levels were significantly higher in all white AT depots than in BAT. Pappa was most highly expressed in the mesenteric depot: levels were 7.5-fold higher in mesenteric than in subcutaneous AT ( p < .001). Although intraabdominal in origin, epididymal and retroperitoneal Pappa expression levels were 69% and 68% lower, respectively, as compared to mesenteric levels ( p < .001). Stc2 RNA expression was significantly higher in all intraabdominal white AT as compared to subcutaneous AT and BAT; levels in epididymal, retroperitoneal, and mesenteric were all more than three-fold higher than in subcutaneous AT ( p < .001) and 12-fold higher than in BAT ( p < .001). Gene expression patterns in bGH and GHR−/− mice mimicked those in WT mice, suggesting that GH does not affect the transcription of the STC2-PAPP-A-IGFBP-4-axis in AT. However, proteins levels of intact IGFBP-4 were significantly increased in bGH mice and decreased in GHR−/− mice, whereas the PAPP-A-generated IGFBP-4 fragment level was unaltered. Conclusion: Expression of Igfbp4, Pappa, and Stc2 differ between AT depots and is generally higher in white AT than in BAT. The transcription appears to occur in a GH-independent manner, whereas IGFBP-4 protein levels are highly influenced by altered GH activity. Highlights: IGFBP-4, PAPP-A and STC2 are expressed in murine adipose tissue in a depot-dependent manner. The proteins appear to play a more pronounced role in white than brown adipose tissue. The regulation of the RNA expressions likely occurs in an GH-independent manner. Interestingly, IGFBP-4 protein levels differ significantly between the genotypes, despite unaltered gene expression levels. Adipose tissue depots appear inherently distinct and cannot be analyzed interchangeably with regard to the IGF system.